Grazing Reduces the Soil-Atmosphere Exchange of Greenhouse Gases During Freeze-Thaw Cycles in Meadow Steppes in Inner Mongolia - Wang, Fangfang; Chen, Yongzhe; Li, Ting; Wang, Cong; Wang, Dongbo; Fu, Bojie; Lv, Yihe; Wu, Xing (Frontiers in Ecology and Evolution, 2021)
Both livestock grazing and soil freeze-thaw cycles (FTCs) can affect the soil-atmosphere exchange of greenhouse gases (GHGs) in grasslands. However, the combined effects of grazing and FTCs on GHG fluxes in meadow steppe soils remain unclear. In this study, we collected soils from paired grazing and enclosed sites and conducted an incubation experiment to investigate the effect of grazing on soil GHG fluxes in the meadow steppes of Inner Mongolia during three FTCs. Our results showed that FTCs substantially stimulated the emissions of soil N2O and CO2 and the uptake of CH4 in the meadow steppes. However, compared with enclosure treatments, grazing significantly reduced the cumulative N2O, CO2 and CH4 fluxes by 13.3, 14.6, and 26.8%, respectively, during the entire FTCs experiment. The soil dissolved organic carbon (DOC) and nitrogen (DON), NH4+-N and NO3–-N, significantly increased after three FTCs and showed close correlations with N2O and CO2 emissions. Structural equation modeling (SEM) revealed that the increase in NO3–-N induced by FTCs dominated the variance in N2O emissions and that DOC strongly affected CO2 emissions during thawing periods. However, long-term grazing reduced soil substrate availability and microbial activity and increased soil bulk density, which in turn decreased the cumulative GHG fluxes during FTCs. In addition, the interaction between grazing and FTCs significantly affected CO2 and CH4 fluxes but not N2O fluxes. Our results indicated that livestock grazing had an important effect on soil GHG fluxes during FTCs. The combined effect of grazing and FTCs should be taken into account in future estimations of GHG budgets in both modeling and experimental studies.